Two major human phenotypes of MICA molecules and their differential activation to NK cells via NKG2D receptor - Luo, Qizhi; Yin, Xiangli; Zhu, Quan; Luo, Weiguang; Liu, Rongjiao; Wei, Leiyan; Zou, Yizhou (Frontiers in Immunology, 2025)
IntroductionThe major histocompatibility complex class I-related gene A (MICA), is a highly polymorphic gene, serve as a crucial role in immune regulator through its interaction with the NKG2D receptor on natural killer (NK) cells. These polymorphisms may influence immune responses, disease susceptibility, and transplant outcomes. However, the precise mechanisms by which MICA polymorphisms modulate NKG2D receptor activation remain poorly understood.MethodsWe analyzed 29 representative MICA polymorphic molecules that cover the most prevalent alleles in the population. These variants were systematically examined through Luminex bead assays, monoclonal antibody binding studies, and NKG2D-Ig fusion protein assays. NKG2D receptor activation was assessed in vitro using NKG2D reporter cells, while NK cell-mediated cytotoxicity was evaluated through NKL cell killing assays against target cells expressing either Type-I or Type-II MICA molecules.ResultsOur analysis identified two major types of MICA polymorphisms based on antigenic epitopes and NKG2D binding characteristics. Type-I MICA characterized by six specific polymorphic site and their associated amino acid variants. exhibited significantly stronger NKG2D receptor binding affinity and more robust receptor activation compared to Type-II polymorphisms. This functional distinction was further corroborated by enhanced NK cells cytotoxicity against target cells expressing Type-I MICA molecules. Importantly, these differences in receptor activation and NK cell killing efficiency were attributable to six critical polymorphic amino acid sites.ConclusionThis study demonstrates the existence of two distinct types of MICA polymorphisms that differentially regulate NKG2D receptor activation and NK cell cytotoxicity. These findings offer new insights into that how genetic variation in MICA may contribute to individual differences in disease susceptibility through immune regulation mechanisms.